Comparative study of offset time schemes over optical burst switching (OBS) - A. Yayah, Abdul Salam (Penerbit UTM Press, 2011)
The dramatic and continuous use of the Internet has increased the network traffic that is needed to be transferred through the Internet network. Optical Burst Switching (OBS) has met the requirements of such demands and is considered as a solution of the issues present in Internet networks. However, there are still some issues in OBS network have not been solved. Minimizing offset time delay is one of these concerns and a lot of research has been introduced in order to solve this issue through using various ways or schemes. In this paper, a description of these schemes and their advantages and disadvantages is presented.